Qualitative transcriptional signature for predicting pathological response of colorectal cancer to FOLFOX therapy. Issue 1 (18th December 2019) - He, Jun; Cheng, Jun; Guan, Qingzhou; Yan, Haidan; Li, Yawei; Zhao, Wenyuan; Guo, Zheng; Wang, Xianlong
Abstract: FOLFOX (5‐fluorouracil, leucovorin and oxaliplatin) is one of the main chemotherapy regimens for colorectal cancer (CRC), but only half of CRC patients respond to this regimen. Using gene expression profiles of 96 metastatic CRC patients treated with FOLFOX, we first selected gene pairs whose within‐sample relative expression orderings (REO) were significantly associated with the response to FOLFOX using the exact binomial test. Then, from these gene pairs, we applied an optimization procedure to obtain a subset that achieved the largest F ‐score in predicting pathological response of CRC to FOLFOX. The REO‐based qualitative transcriptional signature, consisting of five gene pairs, was developed in the training dataset consisting of 96 samples with an F ‐score of 0.90. In an independent test dataset consisting of 25 samples with the response information, an F ‐score of 0.82 was obtained. In three other independent survival datasets, the predicted responders showed significantly better progression‐free survival than the predicted non‐responders. In addition, the signature showed a better predictive performance than two published FOLFOX signatures across different datasets and is more suitable for CRC patients treated with FOLFOX than 5‐fluorouracil‐based signatures. In conclusion, the REO‐based qualitative transcriptional signature can accurately identify metastatic CRC patients who may benefit from the FOLFOX regimen. Abstract : FOLFOX is one of the main chemotherapy regimens for colorectal cancer (CRC), but only half of CRC patients respond to this regimen. The REO‐based qualitative transcriptional signature can accurately identify CRC patients who may benefit from the FOLFOX regimen.